PERAN PEMERINTAH DALAM MENGATASI PENYEBARAN HOAXS JELANG PEMILU - Yandri, Lara Indah; Putra, Roby Hadi (Ensiklopedia of Journal, 2024)
Hoaxes or misinformation are one of the causes of public anxiety, especially before and during general elections. Spreading hoaxes in elections is a strategy to gain public support by vilifying opposing parties, even by reducing public confidence in the legitimacy of the authorities. The negative impact of spreading hoaxes which can trigger social fragmentation needs to be anticipated by building the public's capacity to fight hoaxes. The spread of hoaxes and black campaigns on social media is a crucial problem during the elections because it can reduce integrity and harm democratic values. In conducting this research the author applied qualitative literature methods obtained through a literacy process from various books, articles and journals related to the material involved. discussed. The impact of hoaxes on elections creates public misperceptions, where hoaxes can create wrong perceptions among voters. Influence Voter Choices because false information can influence voter decisions which can have an impact on election results and hoaxes can damage the reputation of the candidate and political party concerned. There are various ways to prevent and overcome the spread of hoaxes, such as formulating laws that regulate hoaxes, including: Law Number 11 of 2008 which has been revised to become Law Number 11 of 2016 concerning Information and Electronic Transactions (UU ITE); Criminal Code (KUHP on Fraudulent Acts Article 378, etc. Apart from this law, the government has also blocked thousands of sites and social media accounts that spread hoaxes. The government is also collaborating with the Press Council and Facebook . Apart from that, the government is also establishing government public relations personnel. The public relations personnel recruited are a mandate from Presidential Instruction Number 9 of 2015, who have public relations and journalistic competencies. The government has even created an official website for internet users to clarify hoax news, namely turnbackhoax.id .Keywords: Hoax, Election, integrity